Strategic engagement and librarians - Smyth, Neil (Palgrave Macmillan, 2015)
The future of the academic book is a strategic engagement issue for librarians. Books might not be stored in or purchased for university libraries; they might not even exist in a physical form. How will academic books be organised and accessed in the future, if they are not in libraries? How will librarians at universities engage academic researchers in strategic conversations about the future of their academic books? This chapter argues that conversations between librarians and academic book authors about the future are more important than ever. It puts the current challenges in context, using data from the Research Excellence Framework and the University of Nottingham library catalogue, identifying the strategic role of librarians in shaping the future of the academic book through strategic engagement.